Radiation Injury: Mechanism of Toxicity and Countermeasures - Soni, Alok Kumar; Soni, Ankita; Upmanyu, Neeraj; Kannan, Gurusamy Mathu; Dongre, Nirmal (Free Radicals and Antioxidants)
This paper aims to review the basic concept of radiation biology and better understand the mechanism of toxicity when interacting with living tissue. The main content of this review includes the source of radiations, unit and measurement, mechanism of tissue injury and possible effects from that exposure; theoretic dose-response curves and their uses in radiation biology; stochastic versus non-stochastic effects of radiation exposure possible acute and chronic radiation exposure effects. Apart from that, we have also reviewed the recent development and progress available as well as under investigation, potential countermeasures compounds against the radiation-induced injury.
Keywords: Radiation biology; Oxidative stress; Inflammation; Acute radiation effects; Chronic radiation effects; Radiation countermeasures